Response of Broilers to Phytobiotic-Fortified Diets Enriched with Lactic Acid Bacteria Serum (LABS) - Monte, Ferdinand; Gaffud, Oliva (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the effectiveness of phytobiotic-fortified diets combined with lactic acid bacteria serum (LABS) as sustainable alternatives to antibiotic growth promoters in broiler production under tropical conditions. Grounded in the concept of gut microbiota modulation and synergistic action of natural feed additives, the research employed a Completely Randomized Design (CRD) involving 150 Cobb 500 broiler chicks distributed across five treatments with three replicates each. Treatments included a control group and four groups receiving diets fortified with moringa, guava, oregano, and lagundi leaf meals at 5% inclusion, supplemented with 2% LABS in drinking water. Data on growth performance, carcass characteristics, environmental conditions, mortality, and economic returns were collected and analyzed using Analysis of Variance (ANOVA) and Least Significant Difference (LSD) tests. Results showed that phytobiotic-LABS supplementation significantly improved body weight and weight gain during later growth stages, with the moringa-fortified group achieving the highest final weight. Feed and water consumption were not significantly affected, indicating improved nutrient utilization rather than increased intake. Carcass characteristics and organ development remained comparable across treatments, confirming physiological safety. Mortality rates were lower in supplemented groups, suggesting enhanced resilience to heat stress. Economically, supplementation increased gross returns, though higher production costs influenced profitability, with the guava-based treatment demonstrating the best cost efficiency. The findings conclude that phytobiotic-fortified diets with LABS are viable and effective alternatives to antibiotics, improving productivity, survivability, and economic outcomes when optimized. This study supports SDG 2 (Zero Hunger), SDG 3 (Good Health and Well-Being), and SGD 12 (Responsible Consumption and Production) by promoting sustainable poultry production and reducing reliance on antibiotics. The sustainability impact lies in enhancing food security, improving farmer income, reducing antimicrobial resistance risks, and supporting environmentally responsible and health-conscious broiler production systems.